Reconceptualizing Japan's Role During Economic Shocks : A Role Theory Analysis of Japan's National Role Conceptions and Shifts during the Global Financial Crisis and the Covid-19 Economic Recession - Pesola, Ella (My University, 2023)
This thesis examines Japan's role within the International Monetary Fund (IMF) and the Chiang Mai Initiative Multilateralization (CMIM) during the global financial crisis (GFC) and the COVID-19 economic recession. The study utilizes role theory and document analysis and content analysis to explore how Japan's national role conceptions and role enactments within these institutions reflect its position within global and regional economic and financial governance structures. The research reveals that Japan's contributions to stabilizing global and regional economic and financial systems during times of crisis have been significant, with its role enactments encompassing supporting institutions and their reform efforts, providing liquidity, and guiding them through experience and leadership. However, Japan's role within these structures has undergone shifts, with its role enactments not always aligning with the role expectations of the institutions. The study highlights the complexity of global and regional financial governance architectures, the power struggles for leadership and responsibility, and the challenge of creating legitimacy and operationalizing loan policies during economic crises. Overall, the research emphasizes the importance of Japan's role in promoting international values and its leadership in multilateral economic cooperation.
Keywords: Global Economic Governance, Regional Economic Governance, Covid-19 Economic Recession, Global Financial Crisis, Role Theory, Japan